Development, Characterization and Evaluation of Cubosomes Loaded Smart Gel for the Treatment of Osteomyelitis using 32 Factorial Design - Gupta, N. Vishal; Jain, Siddharth C; Jain, Vikas; Ravi, Gundawar (Indian Journal of Pharmaceutical Education and Research, 2023)
Aim: The main aim of present study is to formulate cubosomes containing curcumin. Curcumin is a BCS class IV drug which has clinically proven good anti-bacterial property. Materials and Methods: Cubic nanoparticles were prepared by hydrotrope dilution method. Cubosomes were formulated with the glyceryl monooleate and pluronic F-127 as a lipid and surfactant respectively, the obtained formulations were characterized for particle size, entrapment efficiency and zeta potential. Design of Experiment (DoE) technique was used for deriving number of experiments and obtain an optimised formulation, which is further incorporated into smart gel and the smart gels were evaluated for gelation time, gelation temperature, viscosity and in vitro drug release. Results: The particle size of the optimized formulation of cubosomes was 186.27nm, zeta potential -17.5 mV and greater entrapment efficiency (71.24%). In vitro studies were carried out for smart gels loaded with pure drug and optimised formulation (F7) showed good sustained release activity. Conclusion: Hence the optimised formulation (F7) of smart gel shows good potential for treatment of osteomyelitis.
Keywords: Osteomyelitis; Cubosomes; Smart gels; Curcumin; Design of Experiment